Stakeholder Participation Analysis in the Development of Work Breakdown Structure (WBS): A Qualitative Analysis of Health Project Management Practices - Arief Rahman (Ilomata International Journal of Social Science, 2026)
Hospital construction projects involve complex coordination among multiple actors, yet previous studies have paid limited attention to how stakeholder participation shapes the development of Work Breakdown Structure (WBS) within specific healthcare construction settings. This study aimed to examine the forms and levels of stakeholder participation in WBS development and to identify factors influencing stakeholder involvement during project planning. A qualitative case study was conducted in the Dharmais Cancer Hospital construction project. Data collection was conducted through semi-structured interviews with nine key informants representing strategic project organization functions, which includes senior management, project operations, engineering, administration, quantity surveying, building information modeling, and contract management, alongside the project owner representative. Data were analyzed using thematic analysis and validated through triangulation techniques. The findings indicate that stakeholder participation varied across groups. Project owners and key technical actors were actively involved in defining work packages and making planning decisions, whereas some supporting stakeholders participated only at the consultation stage. In several instances, participation tended to become formalistic because decision-making authority remained concentrated among a limited number of actors, while communication and institutional procedures constrained broader involvement. Organizational structure, leadership commitment, communication mechanisms, and information technology support were identified as important factors shaping participation patterns. The study suggests that effective WBS development depends not only on the presence of stakeholders but also on the quality and distribution of their participation. These findings provide practical insights for improving collaborative planning in healthcare construction projects.